Layanan pendampingan terhadap mahasiswa pelaksana program kampus mengajar di kabupaten Bantul - Rochaendi, Endi; Sari, Indah Perdana; Ariyani, Yusinta Dwi; Kholik, Nur; Sholihah, Dyahsih Alin; Ma'mun, Saepul; Mahfud, Mahfud (ABDIMASY: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
The Teaching Campus Program, as part of the Merdeka Belajar-Kampus Merdeka policy, has been successfully implemented to expand opportunities for students to contribute to improving education management. The program's success is supported by the role of Supervising Lecturers, who provide guidance through consultation, assistance, and facilitation. This method enables effective coordination with all education stakeholders, both at the government and school levels. Supervising Lecturers also act as facilitators, educators, and representatives of the Ministry of Education, Culture, Research, and Technology (Kemendikbudristek), including mediating with schools. Through this mentoring, students can function as educators and education support staff, facilitating learning processes akin to permanent teachers and managing administrative, library, and school culture empowerment tasks at their assigned schools. The program demonstrates a significant impact in strengthening the education ecosystem through collaboration among students, lecturers, and schools.